Plants as bioindicators of heavy metal pollution - Sayran A. Qader; Zhian R. Salih (Zanco Journal of Pure and Applied Sciences, 2023)
This research was designed to assess metal deposition (Zn, Cr, As, Cd, Hg and Pb) and modifications in photosynthetic pigments, total nitrogen, protein in six plant species (Brachiaria eruciformis, polypogon monspeliensis, Phragmites australis, Cynodon ductylon, Prosopis farcta and Typha domingensis) near Turaq region which was designated as polluted site and comparing it to control site. The results indicated a significantly increased concentration of studied metals in the contaminated area. Phragmites australis shows maximum accumulation of Cr, As, and Hg. The accumulation of Zn, Pb and Cd were highest in Prosopis farcta, Cynodon ductylon and polypogon monspeliensis, respectively. Pigments and proteins were found in lower amounts in plants grown on polluted soil. Metals were negatively correlated with pigments, total nitrogen and proteins in all of the studied plants. The data demonstrated the existence of metals in the plant body in both regions, indicating that there is a variation in metal absorption capacities.